QUALITY ASSESSMENT OF SF6 INSULATION AT WARU 150 KV GIS COMPARTMENT USING PARTIAL DISCHARGE ION MOBILITY SPECTROMETER - Negara, Yulistya; Mahmudsyah, Syariffuddin; Kurniawan, Ade (Jurnal Teknologi Elektro; Vol 7 No 2 (2008): (July - December) Majalah Ilmiah Teknologi Elektro, 2013)
Almost all of modern gas insulated switchgears (GIS) use sulphur hexafluoride (SF6) as insulation material. Therefore, GIS quality much or less depends on quality of its SF6. Failure however can arise within operation of SF6 GIS due to quality decline of SF6. Quality decline of SF6 in GIS can be recognized by existence of decomposition product of SF6, which may appear due to partial discharge, arc during switching, etc. Therefore quality control of SF6 insulation in GIS is necessary in order to prevent failure occurred due to SF6 quality decline. In this study, quality assessment of SF6 at Waru 150 kV SF6 GIS is done using equipment namely partial discharge ion mobility spectrometer.  This equipment assesses quality of SF6 based on ions mobility. Concentration of decomposition product is then obtained from ion mobility of gas analyzed. For all compartment tested of Waru 150 kV SF6 GIS, it was found that the largest concentration of decomposition product is between 1000-2000 ppmv. Generally, SF6 condition at Waru 150 kV SF6 GIS is normal based on CIGRE standard.
Keywords: GIS, SF6 Ion Mobility Spectromete